Scale Up Usaha Skala Rumah Tangga Bawang Goreng di Kelurahan Kedungkandang - Anies Fuady; Rini Rahayu Kurniati; Ika Nuriyanti; Warsito Warsito; Nisa’us Sholikah; Abdul Rani; Afifuddin Afifuddin; Ita Suhermin Ingsih (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
The problems faced by the household-scale fried onion business 'Siana' were the lack of production equipment in the form of oil filters and product processing methods that do not pay attention to sanitation and hygiene and there is no bookkeeping of business finances. This service aimed to increase the productivity and income of the 'Siana' fried onion small business partners by improving the knowledge and skills of producers in production and financial management. The method of implementing this program is in the form of counseling, training, and assistance to the owners and employees of the 'Siana' fried onion business. The results of implementing the service program include: increasing partners' knowledge about sanitation and hygiene principles; and increasing the understanding and skills of partners for business management with the POAC (Planning Organizing Actuating Controlling) concept.